THE DEVELOPMENT OF CLIENT-BASED CLIENT-BASED COUNSELING PROGRAM DESIGN MODULE WITH POSSIBILITY AND SUSTAINABILITY PRINCIPLES - Mirna Fitri Nur Cahyani Dewi (Polteknik Ilmu Pemasyarakatan, 2019)
Probation Officer has a very strategic role in the Indonesian correctional system. As the spearhead of implementing the correctional function, they have a very large responsibility. Meanwhile, the ratio of the probation officer number to prisoners is still unequal. Moreover, the huge scope of the probation officer’s role implements of their works in the field often met obstacles so that it cannot run optimally. Develop of the module for designing the guidance program to a client is structured as an innovation and strategy to be able to help the probation officer carry out their duties, especially in the matter of client intervention. This module includes a practical guide for probation officer to be able to design a client’s intervention program that is based on client needs by considering aspect of probation officer and client's own capacity (possibility principle) also maximizing the involvement of related parties, namely guarantors/bailsman, families and communities to participate in helping the intervention process that has been designed. These aim to improve the continuous process of the mentoring program (sustainability principle)